From Adaptive Resilience to the Production of the Common. An Analytical Framework for Rethinking Immobility in the Context of Climate Crisis - Alfaro Aramayo, Yolanda; Rocha Medina, Mónica; Salazar Lohman, Huáscar (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2026)
Within risk studies, resilience has become established as a dominant concept linked to adaptation and defined as the capacity to anticipate, absorb, and recover. However, this framework tends to obscure the structural conditions that produce vulnerability, normalizing precariousness through technocratic discourse. This article critically examines how the notion of resilience is employed in climate mobility studies, advancing toward alternative readings that move beyond the dichotomy presenting migration as agency and immobility as a lack of adaptive capacity. The analysis draws on the case of the Pozo de Flores Association in the Upper Valley of Cochabamba, Bolivia—a community water management initiative led by peasant women. The study adopts a qualitative and situated approach, based on in-depth interviews and participatory mapping. Results demonstrate that voluntary immobility can no longer be understood merely as adaptation or community resilience. Rather, it constitutes a conscious political practice of resistance against the capitalist necrotization of life, rooted in collective strategies for territorial defense and the sustenance of life.